Ephemeral waters bodies, fodder and bushfire monitoring in Senegal - Diongue, Djim M. L.; Sall, Amadou; Ouedraogo, Issa (2023)
Climate change poses significant challenges to livestock systems worldwide, requiring urgent and innovative responses to ensure the resilience of these systems and the livelihoods that depend on them. This report presents the water, fodder, bush-fire and transhumance corridor monitoring system as well as the livestock climate information information dissemination in the pastoral zones of Senegal.